Exploring the Association between Schizophrenia and Cardiovascular Diseases: Insights into the Role of Sigma 1 Receptor - Rafcikova, Julie; Nováková, Marie; Stračina, Tibor (Physiological research, 2023)
Contemporary society is characterized by rapid changes. Various epidemiological, political and economic crises represent a burden to mental health of nowadays population, which may at least partially explain the increasing incidence of mental disorders, including schizophrenia. Schizophrenia is associated with premature mortality by at least 13-15 years. The leading cause of premature mortality in schizophrenia patients is high incidence of cardiovascular diseases. The specific-cause mortality risk for cardiovascular diseases in schizophrenia patients is more than twice higher as compared to the general population. Several factors are discussed as the factor of cardiovascular diseases development. Intensive efforts to identify possible link between schizophrenia and cardiovascular diseases are made. It seems that sigma 1 receptor may represent such link. By modulation of the activity of several neurotransmitter systems, including dopamine, glutamate, and GABA, sigma 1 receptor might play a role in pathophysiology of schizophrenia. Moreover, significant roles of sigma 1 receptor in cardiovascular system have been repeatedly reported. The detailed role of sigma 1 receptor in both schizophrenia and cardiovascular disorders development however remains unclear. The article presents an overview of current knowledge about the association between schizophrenia and cardiovascular diseases and proposes possible explanations with special emphasis on the role of the sigma 1 receptor.
Keywords: kardiovaskulární systém; kardiovaskulární nemoci; lidé; Cardiovascular Diseases; Schizophrenia; Cardiovascular System; schizofrenie; Humans